Narrow-band absorption type color radiation refrigeration material and preparation method thereof

CN122668583BActive Publication Date: 2026-10-09武汉简一科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611135134.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-09
Estimated Expiration
2046-07-29

AI Technical Summary

Technical Problem

常规增加柔性树脂或增塑成分的方法可以改善涂层的初始柔韧性,但过量柔性组分可能填充光散射孔隙、降低颗粒与空气之间的折射率差异,还可能带来表面发黏、耐污性下降及长期迁移等问题

Benefits of technology

1、经疏水化处理的二氧化硅分布在PVDF多孔层的孔壁和颗粒界面附近,其低表面能能够降低水对孔壁的润湿程度,减少液态水沿连通孔道向涂层内部渗透。同时,细小的二氧化硅颗粒延长了水分进入涂层的路径,使水分不易在孔隙和界面处大量聚集。由此可减少低温条件下结冰水量,降低水分冻结膨胀对孔壁及颗粒界面的反复冲击。在不明显封闭光散射孔隙的情况下,涂层经过多次冻融循环后仍能保持较完整的多孔结构,因而兼顾了抗冻融性能与太阳光反射性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122668583B_ABST
    Figure CN122668583B_ABST
Patent Text Reader

Abstract

The application discloses a kind of narrow-band absorption type color radiation refrigeration materials and preparation method thereof, it is related to radiation refrigeration material technical field.The method includes: using n-octyl triethoxysilane to carry out surface modification to silica and obtain hydrophobic silica;With n-butyl acrylate and methyl methacrylate copolymerization by using gamma-methacryloyl oxy propyl trimethoxysilane to treat glass short fiber, and obtain flexible coated fiber;After poly (vinylidene fluoride-co-hexafluoropropylene) is dissolved, barium sulfate, the hydrophobic silica, the flexible coated fiber, flaky talcum powder and stearic acid coated nano calcium carbonate are dispersed, with water as non-solvent to carry out phase inversion and obtain porous scattering force layer;Finally, the surface of poly (vinylidene fluoride-co-hexafluoropropylene) solution containing narrow-band absorption solvent dye is coated, dried to form narrow-band absorption color layer, namely obtained.The material has color appearance and high-efficiency radiation refrigeration performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radiation cooling materials technology, specifically to a narrow-band absorption type colored radiation cooling material and its preparation method. Background Technology

[0002] Radiative cooling materials can reduce the temperature of the material surface and the objects they cover by reflecting solar radiation and transferring their own heat to the external environment in the form of infrared radiation. Compared with electrically driven cooling methods, radiative cooling has the advantages of low energy consumption, simple operation, and suitability for large-area building surface applications. To achieve high daytime cooling capacity, the material typically needs to have high reflectivity in the solar radiation band and high emissivity in the mid-infrared band.

[0003] Traditional high-reflectivity radiative cooling materials are mostly white or light-colored, making it difficult to meet the color requirements of architectural decoration, transportation facilities, and outdoor equipment. While adding ordinary pigments can impart color, these pigments typically absorb across a wide range of the solar spectrum, increasing the material's solar energy absorption and thus weakening its radiative cooling effect. Narrow-band absorption coloring methods selectively absorb a portion of visible light corresponding to the target color while preserving the reflectivity of the remaining solar wavelengths as much as possible. This approach achieves a colored appearance while minimizing the adverse effects of the coloring layer on cooling performance. Therefore, controlling the absorption range, distribution, and migration of coloring substances within the coating is a crucial issue that needs to be addressed in the development of colored radiative cooling materials.

[0004] Polyvinylidene fluoride (PVDF) and its copolymers possess weather resistance, chemical corrosion resistance, and good mid-infrared radiation properties, making them suitable as film-forming substrates for solvent-based radiation cooling coatings. Through solvent evaporation, non-solvent-induced phase separation, or a synergistic effect of both, pores of different sizes can be formed within the polymer, combining with inorganic particles to produce multiple scattering of sunlight, thereby enhancing the material's solar reflectivity. However, the porous structure leads to the formation of numerous pore walls, channels, and phase interfaces within the coating, increasing the likelihood of moisture ingress and retention.

[0005] In environments with alternating low temperatures and humidity, moisture entering the pores and interfaces repeatedly freezes and thaws. The volume changes caused by freezing easily create localized stress at the pore walls, the interface between inorganic particles and the polymer matrix. After multiple freeze-thaw cycles, this stress may cause pore wall damage, interface debonding, and microcrack propagation, leading to decreased coating adhesion, surface chalking, or localized peeling. While simply increasing the coating density can reduce moisture ingress, it weakens the light scattering effect generated by the internal pores, potentially resulting in a decrease in solar reflectivity.

[0006] On the other hand, solvent-based polyvinylidene fluoride (PVDF) coatings typically contain a high proportion of inorganic scattering particles. During the coating drying process, solvent evaporation, polymer shrinkage, and particle rearrangement generate internal stress; during subsequent use, the thermal expansion differences between the polymer matrix and inorganic particles, and between the substrate and the substrate itself, create cyclic stress. When the inorganic particle content is high, particles agglomerate, or interfacial stress is concentrated, the coating is prone to microcracks, which continue to propagate under temperature changes or external forces. Conventional methods of adding flexible resins or plasticizers can improve the initial flexibility of the coating, but excessive flexible components may fill light-scattering pores, reduce the refractive index difference between particles and air, and may also lead to problems such as surface stickiness, decreased stain resistance, and long-term migration.

[0007] Furthermore, structural control measures to improve freeze-thaw resistance and toughening measures to improve crack resistance are not independent of each other. Treatments used to reduce moisture ingress and enhance interfacial stability may increase local interfacial stiffness, making the coating more prone to stress concentration during bending or thermal expansion and contraction; while components used to improve flexibility may alter the porous structure, particle dispersion, or spectral selectivity of the coloring layer. Therefore, it is still necessary to provide a method for preparing narrowband absorption-type colored radiation cooling materials that, while maintaining the solar reflectance, mid-infrared emission, and color performance of solvent-based polyvinylidene fluoride materials as much as possible, systematically improves their long-term freeze-thaw resistance and crack resistance, while also considering the structural stability and practical application performance of the coating. Summary of the Invention

[0008] The purpose of this invention is to provide a narrowband absorptive color radiation cooling material and its preparation method, so as to solve the technical problems mentioned in the background art.

[0009] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a narrowband absorptive color radiation cooling material includes the following steps: (1) Surface modification of silica was performed using n-octyltriethoxysilane to obtain hydrophobic silica; (2) The glass short fibers were surface treated with γ-methacryloxypropyltrimethoxysilane, and n-butyl acrylate and methyl methacrylate were copolymerized with the unsaturated groups on the surface of the glass short fibers to obtain polyacrylate flexible coated glass short fibers. (3) Dissolve polyvinylidene fluoride-hexafluoropropylene copolymer in acetone, add barium sulfate, the hydrophobic silica, the polyacrylate flexible coated glass short fiber, flake talc powder and stearic acid coated nano calcium carbonate for dispersion, and then add water as a non-solvent to obtain a porous layer slurry; coat the porous layer slurry, dry it and undergo phase inversion to form a porous scattering load-bearing layer; (4) Dissolve polyvinylidene fluoride-hexafluoropropylene copolymer and narrowband absorber dye in acetone to obtain a colored layer solution; coat the colored layer solution onto the surface of the porous scattering load-bearing layer and dry it to form a narrowband absorber colored layer, thereby obtaining the narrowband absorber colored radiation cooling material.

[0010] Preferably, step (1) includes: drying 100 parts by mass of silica; mixing 4-8 parts by mass of n-octyltriethoxysilane, 120-180 parts by mass of ethanol and 2-5 parts by mass of water, adjusting the pH to 4.5-5.0 with acetic acid, and hydrolyzing at 35-45°C for 30-60 min; adding the silica, reacting at 50-60°C for 1-3 h, filtering, washing, and drying at 70-90°C to obtain the hydrophobic silica.

[0011] Preferably, step (2) includes: 100 parts by weight of glass short fibers were added to an ethanol-water mixture containing 1-2 parts by weight of γ-methacryloyloxypropyltrimethoxysilane and treated for 0.5-2 hours at a pH of 4.5-5.0 and a temperature of 40-50°C. The mixture was then filtered, washed, and dried to obtain silanized glass short fibers. 100 parts by mass of the silanized glass short fibers were dispersed in ethyl acetate. Under inert gas protection, 8.5-11 parts by mass of n-butyl acrylate, 1-3 parts by mass of methyl methacrylate and 0.08-0.15 parts by mass of azobisisobutyronitrile were added. The mixture was reacted at 65-75°C for 4-6 hours. After filtration, washing and drying, the polyacrylate-coated glass short fibers were obtained.

[0012] Preferably, the glass short fiber is alkali-free E glass short fiber with a diameter of 6-10 μm and a length of 80-150 μm.

[0013] Preferably, in step (3), the median particle size of the flaky talc powder is 5-8 μm and the aspect ratio is not less than 10; the median particle size of the stearic acid-coated nano-calcium carbonate is 60-100 nm.

[0014] Preferably, in step (3), based on 100 parts by weight of polyvinylidene fluoride-hexafluoropropylene copolymer, the porous slurry comprises: 35-50 parts by weight of barium sulfate, 3-5 parts by weight of hydrophobic silica, 0.8-1.5 parts by weight of polyacrylate-coated glass short fibers, 2-4 parts by weight of flake talc, 0.8-1.5 parts by weight of stearic acid-coated nano-calcium carbonate, 750-850 parts by weight of acetone, and 85-105 parts by weight of water.

[0015] Preferably, in step (4), based on 100 parts by mass of polyvinylidene fluoride-hexafluoropropylene copolymer, the color layer solution includes 0.25 to 0.60 parts by mass of narrow-band absorbing solvent dye and 600 to 700 parts by mass of acetone; the narrow-band absorbing color layer formed by the color layer solution has a main absorption peak in the visible light range, and the half-width of the main absorption peak is not greater than 100 nm.

[0016] Preferably, the narrow-band absorbent solvent dye is CI Solvent Blue 35, and its dosage is 0.30 to 0.50 parts by weight per 100 parts by weight of polyvinylidene fluoride-hexafluoropropylene copolymer.

[0017] Preferably, the colored layer solution is sprayed with 2 to 3 atomizations, with each wet film thickness not exceeding 20 μm and an inter-pass flash-off time of 2 to 3 min. After spraying, it is dried at 35 to 45°C for 0.5 to 1.5 h, and then vacuum dried at 50 to 60°C for 1 to 3 h.

[0018] A narrowband absorptive color radiation cooling material is prepared by the method described above.

[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. Hydrophobically treated silica is distributed near the pore walls and particle interfaces of the PVDF porous layer. Its low surface energy reduces the wetting degree of water on the pore walls, decreasing the penetration of liquid water into the coating through the interconnected channels. Simultaneously, the fine silica particles lengthen the path for water to enter the coating, preventing water from accumulating in large quantities at the pores and interfaces. This reduces the amount of water freezing at low temperatures and minimizes the repeated impact of water freezing and expansion on the pore walls and particle interfaces. Without significantly sealing the light-scattering pores, the coating maintains a relatively intact porous structure after multiple freeze-thaw cycles, thus achieving a balance between freeze-thaw resistance and solar reflectivity.

[0020] 2. Short glass fibers coated with a flexible polyacrylate layer form a dispersed microscale support structure within the coating. When the coating experiences stress due to solvent evaporation, temperature changes, or substrate deformation, the glass fibers can cross potential crack areas and share the stress. The outer flexible coating layer can mitigate the modulus difference between the rigid fibers and the PVDF matrix, preventing stress concentration at fiber ends or interfaces. Even if fine cracks develop within the coating, the bridging and restraining effect of the fibers reduces the stress intensity at the crack tip, making it less likely for the crack to continue propagating, thereby improving the coating's flexural strength and long-term crack resistance.

[0021] 3. While introducing short glass fibers can improve coating toughness, localized structural gaps can easily form around the fibers. These gaps can become channels for moisture to enter the coating, thus weakening the freeze-thaw resistance provided by the hydrophobic porous structure. To address this issue, flake talc and stearic acid-coated nano-calcium carbonate are added to the system simultaneously. The flake talc extends the water penetration path through interlocking, while the nano-calcium carbonate fills the small gaps around the fibers and between the flakes. The stearic acid layer on its surface further reduces the wettability of these areas. The two functional fillers work together to block pathways and fill micro-gaps, reducing water penetration at the fiber interface without densifying the entire coating. Simultaneously, they make stress transmission around the fibers more uniform, thereby reducing the adverse effects of the crack-resistant structure on freeze-thaw resistance. Attached Figure Description

[0022] Figure 1 This is a low-magnification SEM image of the narrowband absorption type color radiation cooling material prepared in Example 1 of the present invention.

[0023] Figure 2 This is a high-magnification SEM image of the narrowband absorption type color radiation cooling material prepared in Example 1 of the present invention. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1 A method for preparing a narrowband absorptive color radiation cooling material includes the following steps: Step (1): Take 100g of silica with a median particle size of 300nm, dry it at 105℃ for 2h, cool it and seal it for later use. Mix 7g of n-octyltriethoxysilane, 160g of anhydrous ethanol and 4g of deionized water, adjust the pH of the mixture to 4.8 with acetic acid, and stir and hydrolyze it at 40℃ for 50min. Add the dried silica to the above hydrolysate, first stir and disperse it at 800r / min for 15min, and then react it at 55℃ and 400r / min for 2.5h. After the reaction is completed, filter it, wash the filter cake three times with ethanol, dry it under vacuum at 80℃ for 6h, lightly grind it and pass it through a 100-mesh sieve to obtain hydrophobic silica.

[0026] Step (2): Select 100g of alkali-free E-glass short fibers with a diameter of 8μm and an average length of 120μm. Add 1.8g of γ-methacryloyloxypropyltrimethoxysilane to a mixture of 285g of ethanol and 15g of deionized water, adjust the pH to 4.8 with acetic acid, and pre-hydrolyze at room temperature for 30min. Add the glass short fibers, treat at 45℃ and 300r / min for 1h, filter, wash twice with ethanol, and dry at 80℃ for 4h to obtain silanized glass short fibers.

[0027] 100g of the obtained silanized glass short fibers were added to 800g of ethyl acetate and dispersed by stirring at 300r / min. Nitrogen gas was purged for 30min to remove oxygen from the system. Then, a mixture of 10g of n-butyl acrylate, 2.5g of methyl methacrylate, and 0.13g of azobisisobutyronitrile was added. The mixture was heated to 70℃ under nitrogen protection and reacted for 5h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and washed three times with ethyl acetate to remove unbound free polymer. Finally, the mixture was vacuum dried at 60℃ for 8h to obtain polyacrylate-coated glass short fibers.

[0028] Step (3): Take 100g of polyvinylidene fluoride-hexafluoropropylene copolymer and 820g of acetone and add them to a sealed stirring container. Stir at 25℃ and 500r / min for 4h until the polymer is completely dissolved. Add 45g of barium sulfate, 4.5g of hydrophobic silica prepared in step (1), 3.5g of flaky talc with a median particle size of 6μm and an aspect ratio of not less than 10, and 1.3g of stearic acid-coated nano-calcium carbonate with a median particle size of 80nm. Disperse at 1500r / min for 30min. Reduce the speed to 300r / min and add 1.3g of polyacrylate-coated glass short fibers prepared in step (2). Continue stirring for 15min to avoid excessive shearing that could cause fiber breakage. 100g of deionized water was slowly added to the above dispersion system at a rate of approximately 1.5g / min, while stirring at 500r / min during the water addition. After the addition was complete, stirring continued for 20min, followed by standing for 10min to remove bubbles, resulting in a porous slurry. The slurry was then coated onto the surface of a cleaned and degreased aluminum plate, with the wet film thickness controlled at 500μm. The plate was first placed in an environment of approximately 25℃ and 50% relative humidity for 15min to allow acetone to preferentially evaporate and undergo a phase inversion induced by water. It was then dried at 40℃ for 1h and at 55℃ for 2h to form a porous scattering load-bearing layer.

[0029] Step (4): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer to 680g of acetone and stir at 25℃ and 500r / min until completely dissolved. Take a small amount of the above acetone solution, dissolve 0.5g of CISolvent Blue 35 completely, add it to the polymer solution, continue stirring for 30min, and filter through a 200-mesh filter to obtain the colored layer solution. Using a spray gun with a nozzle diameter of 0.8mm, under the conditions of atomization pressure of 0.20MPa and a spraying distance of about 15cm, spray the colored layer solution onto the surface of the porous scattering load-bearing layer. Spray three times, with the wet film thickness of each coat controlled at 15μm. After each coat, flash dry at room temperature for 2.5min. After spraying, dry at 40℃ for 1h, then vacuum dry at 55℃ for 2h, and place in an environment of 23℃ for 24h to obtain a narrow-band absorption type blue radiation cooling material.

[0030] Example 2 A method for preparing a narrowband absorptive color radiation cooling material includes the following steps: Step (1): Take 100g of silica with a median particle size of 300nm, dry it at 105℃ for 2h, cool it and seal it for later use. Mix 5g of n-octyltriethoxysilane, 140g of anhydrous ethanol and 3g of deionized water, adjust the pH of the mixture to 4.8 with acetic acid, and stir and hydrolyze it at 40℃ for 50min. Add the dried silica to the above hydrolysate, first stir and disperse it at 800r / min for 15min, and then react it at 55℃ and 400r / min for 2h. After the reaction is completed, filter it, wash the filter cake three times with ethanol, dry it under vacuum at 80℃ for 6h, lightly grind it and pass it through a 100-mesh sieve to obtain hydrophobic silica.

[0031] Step (2): Select 100g of alkali-free E-glass short fibers with a diameter of 8μm and an average length of 120μm. Add 1.2g of γ-methacryloyloxypropyltrimethoxysilane to a mixture of 285g of ethanol and 15g of deionized water, adjust the pH to 4.8 with acetic acid, and pre-hydrolyze at room temperature for 30min. Add the glass short fibers, treat at 45℃ and 300r / min for 0.8h, filter, wash twice with ethanol, and dry at 80℃ for 4h to obtain silanized glass short fibers.

[0032] 100g of the obtained silanized glass short fibers were added to 800g of ethyl acetate and dispersed by stirring at 300r / min. Nitrogen gas was purged for 30min to remove oxygen from the system. Then, a mixture of 9g of n-butyl acrylate, 1.5g of methyl methacrylate, and 0.09g of azobisisobutyronitrile was added. The mixture was heated to 70℃ under nitrogen protection and reacted for 5h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and washed three times with ethyl acetate to remove unbound free polymer. Finally, the mixture was vacuum dried at 60℃ for 8h to obtain polyacrylate-coated glass short fibers.

[0033] Step (3): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer and 780g of acetone to a sealed stirring container and stir at 25℃ and 500r / min for 4h until the polymer is completely dissolved. Add 38g of barium sulfate, 3.5g of hydrophobic silica prepared in step (1), 2.5g of flaky talc with a median particle size of 6μm and an aspect ratio of not less than 10, and 0.9g of stearic acid-coated nano-calcium carbonate with a median particle size of 80nm in sequence, and disperse at 1500r / min for 30min. Reduce the speed to 300r / min, add 0.9g of polyacrylate-coated glass short fibers prepared in step (2), and continue stirring for 15min to avoid excessive shearing and fiber breakage. Add 90g of deionized water slowly to the above dispersion system at a rate of about 1.5g / min, and keep stirring at 500r / min during the water addition. After the water is added, continue stirring for 20min and let stand for 10min to remove bubbles to obtain a porous slurry. The slurry was scraped onto the surface of a cleaned and degreased aluminum plate, with the wet film thickness controlled at 500 μm. It was first placed in an environment of 25°C and 50% relative humidity for 15 minutes to allow acetone to evaporate preferentially and undergo phase transformation under the induction of water. Then it was dried at 40°C for 1 hour and at 55°C for 2 hours to form a porous scattering load-bearing layer.

[0034] Step (4): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer to 680g of acetone and stir at 25℃ and 500r / min until completely dissolved. Take a small amount of the above acetone solution, dissolve 0.3g of CISolvent Blue 35 completely, add it to the polymer solution, continue stirring for 30min, and filter through a 200-mesh filter to obtain the colored layer solution. Using a spray gun with a nozzle diameter of 0.8mm, under the conditions of atomization pressure of 0.20MPa and a spraying distance of about 15cm, spray the colored layer solution onto the surface of the porous scattering load-bearing layer. Spray two coats, with the wet film thickness of each coat controlled at 15μm. After each coat, flash dry at room temperature for 2.5min. After spraying, dry at 40℃ for 1h, then vacuum dry at 55℃ for 2h. After removal, place in an environment of 23℃ for 24h to obtain a narrow-band absorption type blue radiation cooling material.

[0035] Example 3 A method for preparing a narrowband absorptive color radiation cooling material includes the following steps: Step (1): Take 100g of silica with a median particle size of 300nm, dry it at 105℃ for 2h, cool it and seal it for later use. Mix 6g of n-octyltriethoxysilane, 150g of anhydrous ethanol and 3.5g of deionized water, adjust the pH of the mixture to 4.8 with acetic acid, and stir and hydrolyze it at 38℃ for 45min. Add the dried silica to the above hydrolysate, first stir and disperse it at 800r / min for 15min, and then react it at 55℃ and 400r / min for 2h. After the reaction is completed, filter it, wash the filter cake three times with ethanol, dry it under vacuum at 80℃ for 6h, lightly grind it and pass it through a 100-mesh sieve to obtain hydrophobic silica.

[0036] Step (2): Select 100g of alkali-free E-glass short fibers with a diameter of 8μm and an average length of 120μm. Add 1.5g of γ-methacryloyloxypropyltrimethoxysilane to a mixture of 285g of ethanol and 15g of deionized water, adjust the pH to 4.8 with acetic acid, and pre-hydrolyze at room temperature for 30min. Add the glass short fibers, treat at 45℃ and 300r / min for 1h, filter, wash twice with ethanol, and dry at 80℃ for 4h to obtain silanized glass short fibers.

[0037] 100g of the obtained silanized glass short fibers were added to 800g of ethyl acetate and dispersed by stirring at 300r / min. Nitrogen gas was purged for 30min to remove oxygen from the system. Then, a mixture of 9.5g of n-butyl acrylate, 2g of methyl methacrylate, and 0.1g of azobisisobutyronitrile was added. The mixture was heated to 70℃ under nitrogen protection and reacted for 5h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and washed three times with ethyl acetate to remove unbound free polymer. Finally, the mixture was vacuum dried at 60℃ for 8h to obtain polyacrylate-coated glass short fibers.

[0038] Step (3): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer and 800g of acetone to a sealed stirring container and stir at 25℃ and 500r / min for 4h until the polymer is completely dissolved. Add 40g of barium sulfate, 4g of hydrophobic silica prepared in step (1), 3g of flaky talc with a median particle size of 6μm and an aspect ratio of not less than 10, and 1g of stearic acid-coated nano-calcium carbonate with a median particle size of 80nm in sequence, and disperse at 1500r / min for 30min. Reduce the speed to 300r / min, add 1g of polyacrylate-coated glass short fibers prepared in step (2), and continue stirring for 15min to avoid excessive shearing and fiber breakage. Add 95g of deionized water slowly to the above dispersion system at a rate of about 1.5g / min, and keep stirring at 500r / min during the water addition. After the water is added, continue stirring for 20min and let stand for 10min to remove bubbles to obtain a porous slurry. The slurry was scraped onto the surface of a cleaned and degreased aluminum plate, with the wet film thickness controlled at 500 μm. It was first placed in an environment of 25°C and 50% relative humidity for 15 minutes to allow acetone to evaporate preferentially and undergo phase transformation under the induction of water. Then it was dried at 40°C for 1 hour and at 55°C for 2 hours to form a porous scattering load-bearing layer.

[0039] Step (4): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer to 680g of acetone and stir at 25℃ and 500r / min until completely dissolved. Take a small amount of the above acetone solution, dissolve 0.4g of CISolvent Blue 35 completely, add it to the polymer solution, continue stirring for 30min, and filter through a 200-mesh filter to obtain the colored layer solution. Using a spray gun with a nozzle diameter of 0.8mm, under the conditions of atomization pressure of 0.20MPa and a spraying distance of about 15cm, spray the colored layer solution onto the surface of the porous scattering load-bearing layer. Spray three times, with the wet film thickness of each coat controlled at 15μm. After each coat, flash dry at room temperature for 2.5min. After spraying, dry at 40℃ for 1h, then vacuum dry at 55℃ for 2h, and place in an environment of 23℃ for 24h to obtain a narrow-band absorption type blue radiation cooling material.

[0040] Example 4 A method for preparing a narrowband absorptive color radiation cooling material includes the following steps: Step (1): Take 100g of silica with a median particle size of 300nm, dry it at 105℃ for 2h, cool it and seal it for later use. Mix 8g of n-octyltriethoxysilane, 180g of anhydrous ethanol and 5g of deionized water, adjust the pH of the mixture to 5.0 with acetic acid, and hydrolyze it at 45℃ for 60min. Add the dried silica to the above hydrolysate, first stir and disperse it at 800r / min for 15min, and then react it at 60℃ and 400r / min for 3h. After the reaction is completed, filter it, wash the filter cake three times with ethanol, dry it under vacuum at 90℃ for 6h, lightly grind it and pass it through a 100-mesh sieve to obtain hydrophobic silica.

[0041] Step (2): Select 100g of alkali-free E-glass short fibers with a diameter of 10μm and an average length of 150μm. Add 2g of γ-methacryloyloxypropyltrimethoxysilane to a mixture of 285g of ethanol and 15g of deionized water, adjust the pH to 5.0 with acetic acid, and pre-hydrolyze at room temperature for 30min. Add the glass short fibers and treat at 50℃ and 300r / min for 2.0h. After filtration, wash twice with ethanol and dry at 80℃ for 4h to obtain silanized glass short fibers.

[0042] 100g of the obtained silanized glass short fibers were added to 800g of ethyl acetate and dispersed by stirring at 300r / min. Nitrogen gas was purged for 30min to remove oxygen from the system. Then, a mixture of 11g of n-butyl acrylate, 3g of methyl methacrylate, and 0.15g of azobisisobutyronitrile was added. The mixture was heated to 75℃ and refluxed for 6h under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature, filtered, and washed three times with ethyl acetate to remove unbound free polymer. Finally, the mixture was vacuum dried at 60℃ for 8h to obtain polyacrylate-coated glass short fibers.

[0043] Step (3): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer and 850g of acetone to a sealed stirring container and stir at 25℃ and 500r / min for 4h until the polymer is completely dissolved. Add 50g of barium sulfate, 5g of hydrophobic silica prepared in step (1), 4g of flaky talc with a median particle size of 8μm and an aspect ratio of not less than 10, and 1.5g of stearic acid-coated nano-calcium carbonate with a median particle size of 100nm in sequence, and disperse at 1500r / min for 30min. Reduce the speed to 300r / min, add 1.5g of polyacrylate-coated glass short fibers prepared in step (2), and continue stirring for 15min to avoid excessive shearing and fiber breakage. Slowly add 105g of deionized water to the above dispersion system at a rate of about 1.5g / min, and keep stirring at 500r / min during the water addition. After the water is added, continue stirring for 20min and let stand for 10min to remove bubbles to obtain a porous slurry. The slurry was scraped onto the surface of a cleaned and degreased aluminum plate, with the wet film thickness controlled at 500 μm. It was first placed in an environment of 25°C and 50% relative humidity for 15 minutes to allow acetone to evaporate preferentially and undergo phase transformation under the induction of water. Then it was dried at 40°C for 1 hour and at 55°C for 2 hours to form a porous scattering load-bearing layer.

[0044] Step (4): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer to 700g of acetone and stir at 25℃ and 500r / min until completely dissolved; take a small amount of the above acetone solution, dissolve 0.5g of CISolvent Blue 35 completely and add it to the polymer solution, continue stirring for 30min, and filter through a 200-mesh filter to obtain the colored layer solution. Using a spray gun with a nozzle diameter of 0.8mm, under the conditions of atomization pressure of 0.20MPa and a spraying distance of about 15cm, spray the colored layer solution onto the surface of the porous scattering load-bearing layer, spraying a total of 3 coats, with the wet film thickness of each coat controlled at 15μm, and flash drying at room temperature for 3min after each coat. After spraying, dry at 45℃ for 1.5h, then vacuum dry at 60℃ for 3h, and place in an environment of 23℃ for 24h to obtain a narrow-band absorption type blue radiation cooling material.

[0045] Example 5 A method for preparing a narrowband absorptive color radiation cooling material includes the following steps: Step (1): Take 100g of silica with a median particle size of 300nm, dry it at 105℃ for 2h, cool it and seal it for later use. Mix 4g of n-octyltriethoxysilane, 120g of anhydrous ethanol and 2g of deionized water, adjust the pH of the mixture to 4.5 with acetic acid, and stir and hydrolyze it at 35℃ for 30min. Add the dried silica to the above hydrolysate, first stir and disperse it at 800r / min for 15min, and then react it at 50℃ and 400r / min for 1h. After the reaction is completed, filter it, wash the filter cake three times with ethanol, dry it under vacuum at 70℃ for 6h, lightly grind it and pass it through a 100-mesh sieve to obtain hydrophobic silica.

[0046] Step (2): Select 100g of alkali-free E-glass short fibers with a diameter of 6μm and an average length of 80μm. Add 1g of γ-methacryloyloxypropyltrimethoxysilane to a mixture of 285g of ethanol and 15g of deionized water, adjust the pH to 4.5 with acetic acid, and pre-hydrolyze at room temperature for 30min. Add the glass short fibers, treat at 40℃ and 300r / min for 0.5h, filter, wash twice with ethanol, and dry at 80℃ for 4h to obtain silanized glass short fibers.

[0047] 100g of the obtained silanized glass short fibers were added to 800g of ethyl acetate and dispersed by stirring at 300r / min. Nitrogen gas was purged for 30min to remove oxygen from the system. Then, a mixture of 8.5g of n-butyl acrylate, 1g of methyl methacrylate, and 0.08g of azobisisobutyronitrile was added. The mixture was heated to 65℃ under nitrogen protection and reacted for 4h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and washed three times with ethyl acetate to remove unbound free polymer. Finally, the mixture was vacuum dried at 60℃ for 8h to obtain polyacrylate-coated glass short fibers.

[0048] Step (3): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer and 750g of acetone to a sealed stirring container and stir at 25℃ and 500r / min for 4h until the polymer is completely dissolved. Add 35g of barium sulfate, 3g of hydrophobic silica prepared in step (1), 2g of flaky talc with a median particle size of 5μm and an aspect ratio of not less than 10, and 0.8g of stearic acid-coated nano-calcium carbonate with a median particle size of 60nm in sequence, and disperse at 1500r / min for 30min. Reduce the speed to 300r / min, add 0.8g of polyacrylate-coated glass short fibers prepared in step (2), and continue stirring for 15min to avoid excessive shearing and fiber breakage. Add 85g of deionized water slowly to the above dispersion system at a rate of about 1.5g / min, and keep stirring at 500r / min during the water addition. After the water is added, continue stirring for 20min and let stand for 10min to remove bubbles to obtain a porous slurry. The slurry was scraped onto the surface of a cleaned and degreased aluminum plate, with the wet film thickness controlled at 500 μm. It was first placed in an environment of 25°C and 50% relative humidity for 15 minutes to allow acetone to evaporate preferentially and undergo phase transformation under the induction of water. Then it was dried at 40°C for 1 hour and at 55°C for 2 hours to form a porous scattering load-bearing layer.

[0049] Step (4): Add 100g of polyvinylidene fluoride-hexafluoropropylene copolymer to 650g of acetone and stir at 25℃ and 500r / min until completely dissolved; take a small amount of the above acetone solution, dissolve 0.3g of CISolvent Blue 35 completely and add it to the polymer solution, continue stirring for 30min, and filter through a 200-mesh filter to obtain the colored layer solution. Using a spray gun with a nozzle diameter of 0.8mm, under the conditions of atomization pressure of 0.20MPa and a spraying distance of about 15cm, spray the colored layer solution onto the surface of the porous scattering load-bearing layer, spraying two coats in total, with the wet film thickness of each coat controlled at 15μm, and flash drying at room temperature for 2min after each coat. After spraying, dry at 35℃ for 0.5h, then vacuum dry at 50℃ for 1h, and place in an environment of 23℃ for 24h to obtain a narrow-band absorption type blue radiation cooling material.

[0050] Comparative Example 1 Compared with Example 5, in step (3), 3g of dry silica that has not been treated with n-octyltriethoxysilane is used instead of 3g of hydrophobic silica, and the other raw materials, amounts and preparation conditions are the same as in Example 5.

[0051] Comparative Example 2 Compared with Example 5, step (3) does not involve the addition of polyacrylate-coated glass short fibers, while the remaining raw materials, amounts, and preparation conditions are the same as in Example 5.

[0052] Comparative Example 3 Compared with Example 5, in step (3), 0.8g of alkali-free E-glass short fibers that have not been silanized and polyacrylate coated are replaced with 0.8g of polyacrylate-coated flexible glass short fibers, and the other raw materials, amounts and preparation conditions are the same as in Example 5.

[0053] Comparative Example 4 Compared with Example 5, in step (3), 0.8g of glass short fibers treated only with γ-methacryloyloxypropyltrimethoxysilane but not coated with polyacrylate were used instead of 0.8g of polyacrylate-coated glass short fibers. The other raw materials, amounts and preparation conditions were the same as in Example 5.

[0054] Comparative Example 5 Compared with Example 5, in step (3), 2g of flake talc is not added, only 0.8g of stearic acid-coated nano-calcium carbonate is retained, and the other raw materials, dosages and preparation conditions are the same as in Example 5.

[0055] Comparative Example 6 Compared with Example 5, in step (3), 0.8g of stearic acid-coated nano-calcium carbonate was not added, and only 2g of flaky talc was retained. The other raw materials, dosages and preparation conditions were the same as in Example 5.

[0056] Comparative Example 7 Compared with Example 5, in step (3), 2g of flake talc powder and 0.8g of stearic acid-coated nano-calcium carbonate were omitted, while the remaining raw materials, amounts and preparation conditions were the same as in Example 5.

[0057] Performance testing: Sample preparation: Samples were prepared according to Examples 1-5 and Comparative Examples 1-7, respectively. For optical properties, adhesion and freeze-thaw properties, an aluminum plate with dimensions of 150mm×70mm×1mm was used as the substrate. For flexibility test, an aluminum sheet with dimensions of 120mm×50mm×0.3mm was used as the substrate. After all samples were prepared, they were conditioned for 7 days in an environment with a temperature of (23±2)℃ and a relative humidity of (50±5)%. The dry film thickness of the complete coating was controlled at (75±5)μm. For the same test item, at least 3 parallel samples were set for each group and the arithmetic mean was taken.

[0058] 1. Solar reflectance and near-infrared reflectance: Referring to GB / T 25261—2018 "Reflective Thermal Insulation Coatings for Buildings", an ultraviolet-visible-near-infrared spectrophotometer with an integrating sphere was used, calibrated with a standard white board, to measure the hemispherical spectral reflectance of the complete coating in the range of 300–2500 nm. Five locations were selected for testing on each test board. The solar reflectance was calculated by weighting the reflectance in the range of 300–2500 nm using solar spectral irradiance, and the near-infrared reflectance was calculated by weighting the range of 780–2500 nm.

[0059] 2. Mid-infrared emissivity: A Fourier transform infrared spectrometer with an infrared integrating sphere attachment was used. The gold film was used as a high-reflectance background. The spectral reflectance of the complete coating was measured in the range of 2.5–25 μm, with a spectral resolution set to 4 cm⁻¹. -1 The number of scans was 64. Since the coated aluminum plate can be regarded as an opaque sample in the test band, the spectral emissivity was calculated according to ε(λ)=1-R(λ), and the atmospheric window emissivity was calculated by integrating over the range of 8~13μm with the blackbody radiation intensity of 300K as the weight.

[0060] 3. Narrowband absorption characteristics: Using the 380-780nm reflection spectrum obtained by solar reflectance test, the apparent absorption spectrum is obtained according to A(λ)=1-R(λ) under the condition that the transmittance of the sample is approximately zero. The wavelength with the largest absorption intensity in the visible light range is determined as the position of the main absorption peak. The peak height after local baseline correction on both sides of the absorption peak is used as the reference. The two wavelengths corresponding to the half peak height are read, and the difference between the two is taken as the half peak width of the absorption peak. Each sample is tested 3 times and the average value is taken.

[0061] 4. Water contact angle: Before spraying the colored layer, the porous scattering load-bearing layer was tested. A 5 μL drop of deionized water was added to the sample surface using the seat drop method. The image was acquired and the left and right contact angles were calculated when the droplet contacted the sample for 5 seconds. Five positions were randomly selected for each sample, and the average value of 10 contact angle readings was taken as the static water contact angle.

[0062] 5. Water absorption rate: Referring to GB / T 1034—2008 "Determination of water absorption of plastics", a peelable complete double-layer material was prepared on a polytetrafluoroethylene plate according to the same process. The sample was cut into 50mm×50mm pieces, vacuum dried at 50℃ to constant weight and the mass m0 was recorded. Then, it was completely immersed in deionized water at (23±2)℃ for 24h. After taking it out, the surface water was removed with dust-free absorbent paper, and the mass m1 was weighed within 1min. The water absorption rate was calculated according to W=(m1-m0) / m0×100%. Five samples were tested in each group.

[0063] 6. Pull-off adhesion test: Referring to GB / T 5210—2006 "Paints and Varnishes - Pull-off Adhesion Test", a 20mm diameter pull-off test column and a two-component epoxy adhesive were used. The test column was bonded to the intact coating surface and cured for 24 hours. The coating was then cut along the edge of the test column down to the aluminum substrate. A pull-off tester was used to apply vertical load at a stress increase rate of 0.05MPa / s until failure. Five locations were tested in each group. The adhesion before and after the freeze-thaw test was recorded. The adhesion retention rate was calculated according to the ratio of the adhesion after freeze-thaw to the initial adhesion.

[0064] 7. Enhanced freeze-thaw cycle: Referring to JG / T 25—2017 "Test Method for Temperature Deterioration Resistance of Architectural Coatings", the back and four edges of the test panel were sealed, exposing only the front coating. One cycle consisted of immersion in water at (23±2)℃ for 18h, freezing at (-20±2)℃ for 3h, and heating at (50±2)℃ for 3h. The number of cycles was extended to 50. After the test, the test panel was placed in a standard environment for 24h. Cracking, blistering, and peeling were checked according to GB / T 1766-2008. The most severe item was used to determine the comprehensive appearance grade from 0 to 5, where grade 0 indicates no visible abnormalities and grade 5 indicates severe damage. The adhesion and solar reflectance after freeze-thaw were also measured.

[0065] 8. Flexibility: Refer to GB / T 1731—2020 "Test Method for Flexibility of Paint Film and Putty Film", the complete coating on a 0.3mm thick aluminum sheet is bent around cylindrical shafts of different diameters in sequence. After bending, the bent parts are observed with a 10x magnifying glass. The smallest cylindrical shaft diameter corresponding to the absence of cracks, peeling or exposure of the substrate is taken as the test result. The smaller the value, the stronger the coating's ability to withstand bending deformation.

[0066] Table 1: Compared to Example 5, Comparative Example 1 used untreated silica, resulting in a decrease in the porous layer water contact angle from 109.3° to 79.6°, and an increase in the 24-hour water absorption rate from 2.86% to 7.18%. After 50 freeze-thaw cycles, the adhesion decreased from 1.82 MPa to 1.07 MPa, with a retention rate of only 58.8%, and the reflectivity retention rate also decreased to 90.4%. The initial solar reflectance did not decrease significantly, indicating that the main function of the silica hydrophobication treatment is not simply to increase the initial reflectivity, but rather to reduce the entry and accumulation of water in the porous structure, thereby maintaining the interface integrity and light scattering structure after freeze-thaw cycles.

[0067] Comparative Example 2, without the addition of glass short fibers, had a slightly lower water absorption rate than Example 5, but its minimum bending axis diameter increased from 4 mm to 8 mm. After freeze-thaw cycles, it exhibited a grade 2 appearance defect, indicating that while removing the fibers reduced the fiber interface, it resulted in a lack of crack bridging structure in the coating. Comparative Example 3, with the direct addition of untreated glass short fibers, achieved a minimum bending axis diameter of 10 mm, but its adhesion after freeze-thaw cycles was only 0.87 MPa, indicating that insufficient interfacial bonding between rigid fibers and the polymer makes the fiber ends prone to stress concentration. Comparative Example 4 used silanized but uncoated glass short fibers, and its performance was between that of Comparative Example 3 and Example 5, demonstrating that simply improving interfacial bonding is insufficient to adequately alleviate the deformation difference between the rigid glass fibers and the PVDF-HFP matrix. The flexible polyacrylate coating layer plays a practical role in inhibiting crack initiation and propagation.

[0068] Example 5 contained both flake talc and stearic acid-coated nano-calcium carbonate, with a water absorption rate of 2.86% and an adhesion retention rate of 88.7% after freeze-thaw cycles. Comparative Example 5 retained only stearic acid-coated nano-calcium carbonate, with a water absorption rate increasing to 4.45% and an adhesion retention rate of 75.4%. Comparative Example 6 retained only flake talc, with a water absorption rate of 4.82% and an adhesion retention rate of 72.9%. Comparative Example 7 omitted both, resulting in a further increase in water absorption rate to 6.11% and a decrease in adhesion retention rate to 60.7%. These results indicate that flake talc primarily extends the water penetration path, while stearic acid-coated nano-calcium carbonate primarily fills the tiny gaps around the fibers and between the flakes. When used together, they can more effectively limit water ingress and improve stress transmission near the fibers, thereby mitigating the adverse effects of the fiber-toughened structure on freeze-thaw resistance.

[0069] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a narrowband absorptive color radiation cooling material, characterized in that, Includes the following steps: (1) Surface modification of silica was performed using n-octyltriethoxysilane to obtain hydrophobic silica; (2) The glass short fibers were surface treated with γ-methacryloxypropyltrimethoxysilane, and n-butyl acrylate and methyl methacrylate were copolymerized with the unsaturated groups on the surface of the glass short fibers to obtain polyacrylate flexible coated glass short fibers. (3) Dissolve polyvinylidene fluoride-hexafluoropropylene copolymer in acetone, add barium sulfate, the hydrophobic silica, the polyacrylate flexible coated glass short fiber, flake talc powder and stearic acid coated nano calcium carbonate for dispersion, and then add water as a non-solvent to obtain a porous layer slurry; coat the porous layer slurry, dry it and undergo phase inversion to form a porous scattering load-bearing layer; (4) Dissolve polyvinylidene fluoride-hexafluoropropylene copolymer and narrowband absorber dye in acetone to obtain a colored layer solution; coat the colored layer solution onto the surface of the porous scattering load-bearing layer and dry it to form a narrowband absorber colored layer, thereby obtaining the narrowband absorber colored radiation cooling material.

2. The method for preparing a narrowband absorptive color radiation cooling material according to claim 1, characterized in that, Step (1) includes: drying 100 parts by mass of silica; mixing 4-8 parts by mass of n-octyltriethoxysilane, 120-180 parts by mass of ethanol and 2-5 parts by mass of water, adjusting the pH to 4.5-5.0 with acetic acid, and hydrolyzing at 35-45°C for 30-60 min; adding the silica, reacting at 50-60°C for 1-3 h, filtering, washing, and drying at 70-90°C to obtain the hydrophobic silica.

3. The method for preparing a narrowband absorptive color radiation cooling material according to claim 1, characterized in that, Step (2) includes: 100 parts by weight of glass short fibers were added to an ethanol-water mixture containing 1-2 parts by weight of γ-methacryloyloxypropyltrimethoxysilane and treated for 0.5-2 hours at a pH of 4.5-5.0 and a temperature of 40-50°C. The mixture was then filtered, washed, and dried to obtain silanized glass short fibers. 100 parts by mass of the silanized glass short fibers were dispersed in ethyl acetate. Under inert gas protection, 8.5-11 parts by mass of n-butyl acrylate, 1-3 parts by mass of methyl methacrylate and 0.08-0.15 parts by mass of azobisisobutyronitrile were added. The mixture was reacted at 65-75°C for 4-6 hours. After filtration, washing and drying, the polyacrylate-coated glass short fibers were obtained.

4. The method for preparing a narrowband absorptive color radiation cooling material according to claim 3, characterized in that, The glass short fibers are alkali-free E glass short fibers with a diameter of 6-10 μm and a length of 80-150 μm.

5. The method for preparing a narrowband absorptive color radiation cooling material according to claim 1, characterized in that, In step (3), the median particle size of the flaky talc powder is 5-8 μm and the aspect ratio is not less than 10; the median particle size of the stearic acid-coated nano-calcium carbonate is 60-100 nm.

6. The method for preparing a narrowband absorptive color radiation cooling material according to claim 1, characterized in that, In step (3), based on 100 parts by weight of polyvinylidene fluoride-hexafluoropropylene copolymer, the porous slurry includes: 35-50 parts by weight of barium sulfate, 3-5 parts by weight of hydrophobic silica, 0.8-1.5 parts by weight of polyacrylate flexible coated glass short fibers, 2-4 parts by weight of flake talc, 0.8-1.5 parts by weight of stearic acid coated nano calcium carbonate, 750-850 parts by weight of acetone, and 85-105 parts by weight of water.

7. The method for preparing a narrowband absorptive color radiation cooling material according to claim 1, characterized in that, In step (4), based on 100 parts by mass of polyvinylidene fluoride-hexafluoropropylene copolymer, the color layer solution includes 0.25 to 0.60 parts by mass of narrow-band absorbing solvent dye and 600 to 700 parts by mass of acetone; the narrow-band absorbing color layer formed by the color layer solution has a main absorption peak in the visible light range, and the half-width of the main absorption peak is not greater than 100 nm.

8. The method for preparing a narrowband absorptive color radiation cooling material according to claim 7, characterized in that, The narrow-band absorbent solvent dye is CI Solvent Blue 35, and its dosage is 0.30 to 0.50 parts by weight per 100 parts by weight of polyvinylidene fluoride-hexafluoropropylene copolymer.

9. The method for preparing a narrowband absorptive color radiation cooling material according to claim 7, characterized in that, The colored layer solution is sprayed with 2 to 3 atomizations, with each wet film thickness not exceeding 20 μm and an inter-pass flash-off time of 2 to 3 min. After spraying, it is dried at 35 to 45°C for 0.5 to 1.5 h, and then vacuum dried at 50 to 60°C for 1 to 3 h.

10. A narrow-band absorptive color radiation cooling material, characterized in that, It is prepared by the method described in any one of claims 1-9 above.

Citation Information

Patent Citations

  • Super-hydrophobic self-cleaning radiation self-cooling material and preparation method thereof

    CN112852079A

  • Materials and methods for passive radiative cooling

    US20220090869A1